2012
DOI: 10.1016/j.toxicon.2012.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for the uncoupling of oxidative phosphorylation by juliprosopine on rat brain mitochondria

Abstract: Prosopis juliflora, popularly known as Algaroba, is a major problem because the lack of food during the driest times of the year and its high palatability and nutritional value make its fruits (pods) much appreciated by cattle, goats, sheep and other animals. However, the consumption of this plant for long periods can cause a disease called cara-torta (pie face), which is characterized by cranial nerve dysfunction, mainly due to the degeneration and disappearance of neurons in the trigeminal motor nucleus. Alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 27 publications
0
18
0
1
Order By: Relevance
“…Studies in isolated mitochondria of rat brains showed that juliprosopine stimulates stage-4 cellular respiration and alters the mitochondrial membrane potential and ATP production by inhibiting complex I of the respiratory chain (Maioli et al 2012). In our previous studies, we demonstrated that subtoxic doses of alkaloidal extract (TAE) induce alteration of mitochondrial shape and size and that the alkaloidal fraction (F32) induces shortened and disintegrating mitochondria cristae in neuron/glial cell co-cultures (Silva et al 2013).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies in isolated mitochondria of rat brains showed that juliprosopine stimulates stage-4 cellular respiration and alters the mitochondrial membrane potential and ATP production by inhibiting complex I of the respiratory chain (Maioli et al 2012). In our previous studies, we demonstrated that subtoxic doses of alkaloidal extract (TAE) induce alteration of mitochondrial shape and size and that the alkaloidal fraction (F32) induces shortened and disintegrating mitochondria cristae in neuron/glial cell co-cultures (Silva et al 2013).…”
Section: Discussionmentioning
confidence: 96%
“…This response was best characterized in a model of neuron/glial cell co-culture by neuronal death, astrogliosis, microgliosis, cytoskeleton disruption, mitochondrial damage and vacuolation induction (Silva et al 2013). Maioli et al (2012) investigated the action of juliprosopine in isolated rat brain mitochondria and determined that it stimulated state-4 respiration, affected the membrane potential and ATP production, and that these changes were mainly attributed to modifications in the inner mitochondrial membrane. However, the involvement of these cellular alterations and the mechanism of death induced by these alkaloids have not yet been clarified.…”
mentioning
confidence: 99%
“…While not certain, it appears plausible that the neuromuscular disease observed in poisoned ruminants is caused by some combination of these alkaloids. Juliprosopine is present in all parts of the plant, including the fruit (Ahmad et al 1991) and in a recent study it was demonstrated that this alkaloid interferes with the bioenergetics of rat brain mitochondria, causing a reduction in ATP synthesis and cell death (Maioli et al 2012). Damage to plasma membranes can also occur as was previously demonstrated with erythrocytes subjected to alkaloids from P. juliflora (Kandasamy et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…They play a key role in cell survival because they represent the major site of eukaryotic oxidative metabolism and also participate in apoptotic and necrotic pathways (Desaguer and Martinou, 2000;Nicholls and Ferguson, 2002). Various compounds capable of promoting changes in oxidative phosphorylation have been described in the scientific literature (Wallace and Starkov, 2000;Castanha-Zanoli et al, 2012;Maioli et al, 2012). Among these are uncoupling agents, which increase mitochondrial inner membrane permeability to protons, thus compromising electrochemical proton gradient formation and therefore ATP production and inhibitors, which interfere with ATP synthesis coupled to respiration, preferably operating in the respiratory chain complexes or in the F o F 1 -ATPase (Nicholls and Ferguson, 2002).…”
Section: Discussionmentioning
confidence: 99%